The clinical and neurophysiological characteristics of the deja vu phenomenon in epilepsy - P. N. Vlasov; A. V. Chervyakov; G. R. Drozhzhina; М. V. Antonyuk; N. V. Orekhova; V. V. Gnezditsky; T. Yu. Noskova; P. A. Fedin (Неврология, нейропсихиатрия, психосоматика, 2014)
Objective: to study the clinical and neurophysiological characteristics of the deja vu phenomenon in epilepsy. Patients and methods. The manifestations of the dВjЕ vu phenomenon were compared in 154 examinees in two groups: 1) 139 healthy individuals and 2) 25 patients with epilepsy (mean age 25.17±9.19 years; women, 63.2%) The characteristics of the phenomenon were determined, by questioning the examinees; 12—16-hour ambulatory electroencephalogram (EEG) monitoring was made. Results. The deja vu phenomenon occurred with cryptogenic and symptomatic focal epilepsy with equal frequency; however, the phenomenon was also seen in the idiopathic generalized form of the latter and could be concurrent virtually with any types of seizures and observed as an individual seizure and in the structure of a partial and secondarily generalized seizure. In epileptic patients, the main clinical characteristics of the deja vu vu phenomenon are its frequency, fear before its onset, and emotional coloring. The most important criterion is a change in the characteristics of deja vu vu: prolongation, more frequencies, and the emergence of negative emotions. On EEG, the phenomenon was characterized by the onset of polyspike activity in the right temporal leads and, in some cases, ended with slow-wave, theta-delta activity in the right hemisphere.